PENINGKATAN KETERAMPILAN KOMUNIKASI MATEMATIS PESERTA DIDIK PADA PEMBELAJARAN MATEMATIKA REALISTIK - Palinussa, Anderson Leonardo; Ngilawajan, Darma Andreas (Program Studi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan Universitas Pattimura, 2023)
Communication skills are very important in learning to live in the 21st century, one of which is mathematical communication skills. Mathematical communication is one of the standard processes in learning mathematics. The purpose of this research is to analyze the mathematical communication skills after students receive realistic learning based on coastal potential. The research method was carried out using quasi-experimental research with pretest and posttest control groups. This research was conducted at three junior high schools in West Seram District with a sample of 120 student participants. The instrument developed was a matter of mathematical communication skills as much as 5 questions. Data analysis was carried out namely descriptive statistics, data requirements test including normality test and homogeneity test, then the hypothesis was tested with t-dependent and Wilcoxon tests. At this stage to obtain data on the results of tests of mathematical representation and communication abilities, scoring will be carried out on student's answers for each item. The findings show that there are differences in students' mathematical problem-solving and communication abilities taught by coastal and conventional RME-based learning. From the two learning models used it is proven that RME learning based on coastal potential is more influential and more effective than conventional learning on mathematical communication skills. There are differences in improving mathematical communication skills using the RME learning model based on coastal potential and conventional learning. Thus RME based on coastal potential is recommended for improving students' mathematical communication skills